2000
DOI: 10.1007/s004280000264
|View full text |Cite
|
Sign up to set email alerts
|

Rat cytomegalovirus replication in the salivary glands is exclusively confined to striated duct cells

Abstract: The salivary gland is the preferred organ for cytomegalovirus (CMV) replication and viral persistence. In order to identify the nature of infected cells and to study viral replication in more detail, several experiments were conducted. Using the rat CMV (RCMV) model, acutely infected young adult rats (6 weeks of age) and new-born rats (3 days of age) were infected, and submandibular, parotid and sublingual glands were harvested at different time points after infection. For identification of the nature of infec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
17
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 41 publications
4
17
0
Order By: Relevance
“…3). This finding is not surprising, since previous studies had demonstrated that RCMV takes approximately 14 days to establish infection in SMG (5,6,17,26). Approximately 11% of the RCMV genes are expressed at 14 days p.i., and this number increases to nearly 25% by day 21, which includes genes expressed with IE, E, and L kinetics.…”
Section: Resultssupporting
confidence: 54%
See 1 more Smart Citation
“…3). This finding is not surprising, since previous studies had demonstrated that RCMV takes approximately 14 days to establish infection in SMG (5,6,17,26). Approximately 11% of the RCMV genes are expressed at 14 days p.i., and this number increases to nearly 25% by day 21, which includes genes expressed with IE, E, and L kinetics.…”
Section: Resultssupporting
confidence: 54%
“…RCMV infects a number of different cell types both in vivo and in vitro, including EC, SMC, epithelial cells, fibroblasts, and macrophages (17,28). Similar to HCMV, the RCMV genome is about 230 kbp and includes 167 predicted ORFs (29).…”
Section: Resultsmentioning
confidence: 99%
“…We have utilized a rat cytomegalovirus (RCMV) infection system to model a number of human diseases associated with HCMV infections, including solid-organ transplant rejection and restenosis following angioplasty (26, 27, 29-31, 36-39, 45, 46, 56, 58, 62-64). Similar to human infection, infection of immunocompetent rats leads to a limited subclinical infection that persists lifelong in host bone marrow and columnar epithelial cells of the salivary glands (28). RCMV infection of immunocompromised rats (i.e., rats undergoing immunosuppressive treatment for the prevention of allograft rejection) leads to infection of most host tissues and organs.…”
mentioning
confidence: 99%
“…3–15 Both acinar and ductal salivary epithelial cells can be infected by hCMV. 5,1012 After infection, hCMV can remain latent for the rest of the host’s life, maintaining the viral genome without the production of infectious virions. 1618 The hCMVp is a frequently used enhancer/promoter in many gene transfer vectors.…”
Section: Introductionmentioning
confidence: 99%